2014
DOI: 10.1364/oe.22.018310
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-artifact-free phase retrieval with the transport of intensity equation II: applications to microlens characterization

Abstract: Boundary conditions play a crucial role in the solution of the transport of intensity equation (TIE). If not appropriately handled, they can create significant boundary artifacts across the reconstruction result. In a previous paper [Opt. Express 22, 9220 (2014)], we presented a new boundary-artifact-free TIE phase retrieval method with use of discrete cosine transform (DCT). Here we report its experimental investigations with applications to the micro-optics characterization. The experimental setup is based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…Such systems enable real-time QPI with nanometric sensitivity and millisecond temporal resolution. These new TIE systems have been successfully applied to investigations of drug-induced morphology changes and phagocytosis of macrophages [36], imaging of cellular dynamics of breast cancer cells [37], and characterization of micro-optical elements [45]. Despite the advantages and promising results obtained, the translation of these TIE systems into clinical and biological laboratories is still impeded owing to its complex and bulky optical configuration as well as high costs for the hardware (e.g., SLM, ETL) and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems enable real-time QPI with nanometric sensitivity and millisecond temporal resolution. These new TIE systems have been successfully applied to investigations of drug-induced morphology changes and phagocytosis of macrophages [36], imaging of cellular dynamics of breast cancer cells [37], and characterization of micro-optical elements [45]. Despite the advantages and promising results obtained, the translation of these TIE systems into clinical and biological laboratories is still impeded owing to its complex and bulky optical configuration as well as high costs for the hardware (e.g., SLM, ETL) and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…In our implementation, we used an open‐source fast Fourier transform‐based TIE solver (http://www.scilaboratory.com/h-col-123.html) to recover the phase image. The accuracy of this method has been validated using microlens array . As we can record multiplane information in high speed, the reported approach may be able to recover the phase images of fast‐moving samples such as cilia in a postacquisition processing manner.…”
Section: Multichannel Microscopymentioning
confidence: 94%
“…Besides, when the sample is illuminated with spatially partially coherent light from an optical condenser, TIE is able to achieve improved spatial resolution over the coherent diffraction limit as the angular content of the illumination contributes to the lateral resolution 38 . Because of its numerical simplicity and flexible experimental configuration, TIE-based QPI approaches have found wide-ranging biomedical and technical applications, such as quantitative monitoring of cell growth in culture 40,41 , investigations of cellular dynamics and toxin-mediated morphology changes 33,34 , and characterization of optical elements 42,43 . Although these works have demonstrated that it is possible to acquire accurate and speckle-free phase images under partially coherent illuminations, two fundamental limits still prevail: First, the phase reconstruction is strongly sensitive to low frequency artifacts, as a result of low frequency noise amplification in the direct inversion of the TIE (inverse Laplacian) 44,45 .…”
Section: Introductionmentioning
confidence: 99%